Road Sign as Understood by Indonesian Student in Melbourne, Australia - Masykar, Tanzir (Akademi Komunitas Negeri Aceh Barat, 2022)
AbstractIndonesian students who learn in Australian university and has an Indonesian driving licence are eligible to drive in Australian road. For the state of Victoria, the students can drive in the Victorian roads for six months after arrival without needing to convert their licence to Australian licence. However, Indonesian students may not well aware of the road signs used in Victorai due to different sign system between Indonesia and Australia. This study aims to learn how well Indonesian student in Australia understand the various road sign when they drive the Victorian road. The study used participant observant as its method in which the participant experience the phenomenon firsthand. The results indicates that the road sign used in Vcitoraian roads, even though massive, are relatively easy to be understood. The road signs are comprehensive and inclusive of all types of raod users including cyclist and pedesntrian. Colour coding of the road signs resemble those used in the traffic light which makes them intuitive even for drivers with non-Australian licence. Keywords:Road sign, Indonesian students, Victorian roads__________________________ AbstrakPelajar Indonesia yang belajar di universitas Australia dan memiliki SIM Indonesia berhak mengemudi di jalan Australia. Untuk negara bagian Victoria, para siswa dapat mengemudi di jalanan Victoria selama enam bulan setelah kedatangan tanpa perlu mengubah SIM mereka menjadi SIM Australia. Namun, pelajar Indonesia mungkin tidak begitu paham dengan rambu-rambu jalan yang digunakan di Victorai karena sistem rambu yang berbeda antara Indonesia dan Australia. Penelitian ini bertujuan untuk mempelajari seberapa baik pelajar Indonesia di Australia memahami berbagai rambu lalu lintas saat mereka berkendara di jalan Victoria. Penelitian ini menggunakan metode partisipan observant dimana partisipan mengalami fenomena secara langsung. Hasil menunjukkan bahwa rambu jalan yang digunakan di jalan Vcitoraian, meskipun masif, relatif mudah dipahami. Rambu-rambu jalan komprehensif dan mencakup semua jenis pengguna jalan termasuk pengendara sepeda dan pejalan kaki. Kode warna rambu-rambu jalan mirip dengan yang digunakan di lampu lalu lintas yang menjadikannya intuitif bahkan untuk pengemudi dengan SIM non-Australia. Kata Kunci:Rambu-rambu jalan, Mahasiswa Indonesia, Jalan Victoria